2016
DOI: 10.18357/jcs.v38i2.15449
|View full text |Cite
|
Sign up to set email alerts
|

Development of Menu Planning Resources for Child Care Centres: A Collaborative Approach

Abstract: Well-designed menus in child care centres include nutritious meals and snacks necessary for the optimum health, growth, and lifelong healthy eating behaviours of young children. With pending government food and nutrition standards, a need was identified for comprehensive, relevant, user-friendly menu planning resources. Therefore, guided by an action research model, this study identified current menu planning practices, determined the needs and expectations for menu planning resources, and developed menu plann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…When examining the self‐reported menu planning practices of services, only 43% of menu planners were fully responsible for planning the menu. This finding is consistent with other studies that have identified involvement from others, including managers, other service staff, parents and nutritionists in the planning of service menus . Despite being responsible for menu planning, a large proportion of menu planners report they do not have sufficient allocated time to undertake menu planning.…”
Section: Discussionsupporting
confidence: 90%
“…When examining the self‐reported menu planning practices of services, only 43% of menu planners were fully responsible for planning the menu. This finding is consistent with other studies that have identified involvement from others, including managers, other service staff, parents and nutritionists in the planning of service menus . Despite being responsible for menu planning, a large proportion of menu planners report they do not have sufficient allocated time to undertake menu planning.…”
Section: Discussionsupporting
confidence: 90%
“…Four of these questions were included in the director survey. This approach preempted the expectation that most participants responding to the FoodChecker survey would be cooks but that it was also important to seek insights from directors who often play a role in menu planning [25,46].…”
Section: Foodchecker Survey Designmentioning
confidence: 99%
“…The implementation and effectiveness of web-based health promotion tools in achieving public health impact is largely determined by end-user engagement [ 45 ]. In the childcare setting, users of web-based menu planning tools are most likely to be staff members who plan, prepare, and provide food for children—namely childcare cooks and directors [ 25 , 46 ]. However, little is known about how these users engage with web-based menu planning tools to support healthy food provision.…”
Section: Introductionmentioning
confidence: 99%
“…Childcare centres’ menus provide information about their food service, which usually consists of two meals and two snacks, and most Saskatchewan centres prepare food on site. Well-planned menus are essential for meeting children’s nutritional needs and developing lifelong healthy eating habits ( Mann et al, 2013 ). Infrequent revision limits children’s experience with new foods, textures and flavours.…”
Section: Introductionmentioning
confidence: 99%
“…Menu-planning guidelines are vital in ensuring that young children (age 2–5) consume nutritious meals and snacks at the childcare settings ( Nikolopoulos, 2012 ). A balanced and nutritious diet at a young age is essential for health and proper growth ( Mann et al, 2013 ). Menu guidelines allow menu planners to select a variety of healthy foods that meet children’s daily nutrition requirements.…”
Section: Introductionmentioning
confidence: 99%